COVID-19 and the Health Workforce. (February 2021) - Armstrong, David; Moore, Jean; Fraher, Erin P.; Frogner, Bianca K.; Pittman, Patricia; Spetz, Joanne
The health workforce has been greatly affected by COVID-19. In this commentary, we describe the articles included in this health workforce research supplement and how the issues raised by the authors relate to the COVID-19 pandemic and rapidly changing health care environment.